Research of methods for determining the accuracy of metrological measurements - Kozhevnikov, Andrii; Bilous, Nataliya (Technology audit and production reserves (Online), 2022)
The object of research in this work are individual branches and processes of metrology, namely algorithms and methods of global positioning, analysis and research of individual processes, and their implementation in the software model to analyze their accuracy. The existing problem is that some methods or devices that produce results based on these methods are not accurate enough or their accuracy is affected by a number of factors that worsen the result. During the work the methods and approaches of the global positioning system were analyzed, such as: precise point positioning, relative positioning of GPS, static and fast static GPS-shooting and Stop-and-go shooting. Approaches were also divided into static and kinematic. Among the methods, the method of precise point positioning was chosen, as the most common and used among ordinary GPS users, for more detailed research and analysis of accuracy. Development methods are based on the means of interaction with open GPS services, and C#, ASP.NET Core, Angular framework, and development environment Visual Studio Code and Visual Studio 2022. In order to implement all the necessary functionality, the subject area was analyzed, the methods of determining metrological accuracy in general and within the system of global positioning as a direct object of work were considered. As a result of the work the analysis and modelling of the subject area was carried out, the methods of the global positioning system and the software system for the analysis of the accuracy of one of the GPS methods were investigated. The analysis results provided by the software help to understand the accuracy of the method and the GPS receivers that use it on different devices. Об’єктом дослідження у роботі є окремі галузі та процеси метрології, а саме алгоритми та методи системи глобального позиціювання, аналіз та дослідження окремих процесів, та їх реалізація в програмній моделі для аналізу їх точності. Існуюча проблема полягає в тому, що деякі методи або пристрої, які видають результати на основі цих методів є недостатньо точними або на їх точність впливає ряд факторів, що погіршує результат. Під час роботи було проаналізовано методи та підходи системи глобального позиціонування, такі як: позиціонування точки (precise point positioning), відносне позиціонування GPS, статична та швидка статична GPS-зйомки та зйомка Stop-and-go. Також підходи були поділені на статичні та кінематичні. Серед методів було обрано метод precise point positioning, як самий розповсюджений та використовуваний серед звичайних користувачів GPS, для більш детального дослідження та аналізу точності. Методи розробки базуються на засобах взаємодії з відкритими сервісами GPS, й мовах C#, ASP.NET Core, фреймворку Angular, та середовищі розробки Visual Studio Code й Visual Studio 2022. Для реалізації усього необхідного функціоналу була проаналізована предметна область, розглянуті методи визначення метрологічної точності в цілому та в рамках системи глобального позиціонування як безпосереднього об’єкту роботи. В результаті роботи було проведено аналіз та моделювання предметної області, досліджено методи систему глобального позиціонування та програмна система для аналізу точності одного з методів GPS. Надані результати аналізу за допомогою програмного забезпечення допомагають зрозуміти точність методу та GPS приймачів, що його використовують, на різних пристроях.